Indirect Determination of Amitriptyline Hydrochloride by Square Wave Voltammetry of SnCl2.2H2O - Towfiq amine, Suham; Ibrahim, Ali; Ahmed Mohammed, Asmaa (Tikrit Journal of Pharmaceutical Sciences, 2023)
A simple, fast and sensitive electroanalytical method consist studying the square wave of SnCl2.2H2O at hanging mercury dropping electrode in aqueous solution for the indirect determination of (AMI) drug. SnCl2.2H2O has revealed a major reduction potential at (-0.450) Volt against the reference electrode (Ag/AgCl/Sat.KCl). The calibration curve in the Phosphate buffer as the supporting electrolyte at pH=2 was constracted. The range concentrations up to (0.99X10-5–9.91X10-5) M, the correlation coefficient (r= 0.9989) and then studied the decreased of peak current of the drug by the (HMDE) behavior in the presence of SnCl2.2H2O. Results were as follow: The calibration curves were (0.316 X10-6 -3.136 X10-6) M and thismethods was successfully applied to determination of AMI in apharmaceutical formulations.